Convergence Theorems for G-Nonexpansive Mappings in CAT(0) Spaces Endowed with Graphs: Watcharapong Anakkamatee, Buris Tongnoi - Team, Support (Thai Journal of Mathematics, 2019)
In this paper, we introduce the concept of a CAT(0) space endowed with a graph. Browder's convergence theorem and Halpern iteration process for G-nonexpansive mappings in an underlying space will be presented. This result extends and generalizes the result of Tiammee, Kaewkhao and Suantai (2015).